2018
DOI: 10.1055/a-0638-8255
|View full text |Cite
|
Sign up to set email alerts
|

Six New neo-Clerodane Diterpenoids from Aerial Parts of Scutellaria barbata and Their Cytotoxic Activities

Abstract: Six new neo-clerodane diterpenoids (1: -6: ), scutebatas X - Z, A-C, along with twelve known ones (7: -18: ) were obtained via the phytochemical investigation of the aerial parts of . Their structures were established by detailed spectroscopic analysis. The absolute configurations of 1: and 2: , as the representative members of this type, were identified based on a circular dichroic exciton chirality method. Moreover, in vitro cytotoxicity of compounds 1: -6: were evaluated against three human cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Compound 1 (Figure 1) 5.83) to C(3) and C(1'''), HÀ C(7) (δ(H) 5.53) to C(6) and C(1'') revealed that the two nicotinoyloxy groups were attached to C(1) and C(7), respectively. Based on all of the data the structure of compound 1 was established as shown in Figure 1 and compound 1 named as barbatin H.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 (Figure 1) 5.83) to C(3) and C(1'''), HÀ C(7) (δ(H) 5.53) to C(6) and C(1'') revealed that the two nicotinoyloxy groups were attached to C(1) and C(7), respectively. Based on all of the data the structure of compound 1 was established as shown in Figure 1 and compound 1 named as barbatin H.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Phytochemical investigations on S. barbata showed that the main constituents contained flavonoids, [2] terpenoids, [2,3] and polysaccharides. [4] In recent years, a series of neo-clerodane diterpenoids with cytotoxic [5,6] activities had been isolated from S. barbata, which indicated that they might be a potential chemical structure of antitumor agent. However, very few concrete studies had reported on the effects of those different structural neo-clerodane diterpenoids on cytotoxicity against human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phenylpropanoids [70,80], phenolic compounds, saccharides, and steroids have been isolated from RC [50,51,[80][81][82][83]. It was reported that diterpenoids [84,85] and essential oils [86] were also found in RS. In addition to alkaloids, CP also contains sterols, esters, triterpenes and other compounds [87][88][89][90].…”
Section: Other Chemical Componentsmentioning
confidence: 99%
“…Diterpenoid alkaloids are the most widely reported compounds from S. barbata with cytotoxic activities tested on cancer cell lines. Their in vitro cytotoxicities have been identified on at least one of the following cancer cell lines including HONE-1 nasopharyngeal, KB oral epidermoid carcinoma, HT29 colorectal carcinoma, 19 -22,29,30,35 -37,39,53,54 HL-60 leukemia, 27,31,32,40 SK-BR-3 breast adenocarcinoma, 32 K562 erythromyeloblastoid leukemia, HepG2 and SMMC-7721 hepatocellular carcinoma, 3,23,24,39 A549 lung adenocarcinoma, 3,23 LNCaP prostate cancer, SK-MEL-2 melanoma, 39 MCF-7 breast adenocarcinoma, 24,37,39 SGC7901 gastric cancer, 33 LoVo, 24 HCT-116, 24,28 and SW480 colon adenocarcinoma cells 32 with IC 50 values ranging from 2.0 to over 100 µM. The 6-(2,3-epoxy-2-isopropyl- n -propoxyl) barbatin C (Figure 3) was the most cytotoxic neo-clerodane diterpenoid reported so far with IC 50 as low as 2.0 µM to KB oral epidermoid cancer cells.…”
Section: Phytochemical and Pharmacological Properties Of Scutellaria Barbatamentioning
confidence: 99%